phân tích đa thức thành nhân tử
A = \(x^2-x-1991\cdot1992\)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(=\left(6x^2-3x\right)+\left(4x-2\right)\)
\(=3x\left(2x-1\right)+2\left(2x-1\right)\)
\(=\left(3x+2\right)\left(2x-1\right)\)
\(=6x^2-3x+4x-2=6x\left(x-2\right)+2\left(x-2\right)=2\left(3x+2\right)\left(x-2\right)\)
\(a^3+a+30\)
\(=a^3+3a^2-3a^2-9a+10a+30\)
\(=\left(a+3\right)\left(a^2-3a+10\right)\)
\(x^3+x^2+100\)
\(=x^3+5x^2-4x^2-20x+20x+100\)
\(=\left(x+5\right)\left(x^2-4x+20\right)\)
a) \(4\left(x+y\right)\)
b) \(\left(x-3y\right)^2\)
c) \(x^3-x-x^2+1=x\left(x^2-1\right)-\left(x^2-1\right)=\left(x^2-1\right)\left(x-1\right)=\left(x-1\right)\left(x+1\right)\left(x-1\right)\)
a) \(4 (x + y)\)
b) \((x - 3y)^2\)
c) \(x^3 - x - x^2 + 1 = x (x^2 - 1) - (x^2 - 1) = (x^2 - 1) (x - 1) = (x - 1) (x + 1) (x - 1)\)
a) \(49-x^2-y^2+2xy=49-\left(x^2-2xy+y^2\right)=49-\left(x-y\right)^2=\left(7-x+y\right)\left(7+x-y\right)\)
b) \(\left(x-3\right)+2x\left(3-x\right)^2=\left(x-3\right)+2x\left(x-3\right)^2=\left(x-3\right)\left[1+2x\left(x-3\right)\right]=\left(x-3\right)\left(2x^2-6x+1\right)\)
a)\(3xy-6y=3y\left(x-2\right)\)
b)\(x\left(x+y\right)+2x+2y=x\left(x+y\right)+\left(2x+2y\right)=x\left(x+y\right)+2\left(x+y\right)=\left(x+y\right)\left(x+2\right)\)
c)\(y^2-81=y^2-9^2=\left(y-9\right)\left(y+9\right)\)
a)`3xy-6y`
`=3y(x-2)`
b)`x(x+y)+2x+2y`
`=x(x+y)+2(x+y)`
`=(x+y)(x+2)`
c)`y^2 -81`
`=y^2-9^2`
`=(y-9)(y+9)`
Ta có: A = x2 - x - 1991.1992
=> A = x2 - x - 1991 . 1991 - 1991
=> A = (x2 - 19912) - (x + 1991)
=> A = (x + 1991)(x - 1991) - (x + 1991)
=> A = (x + 1991)(x - 1991 - 1)
=> A = (x + 1991)(x - 1992)